Risk analysis of pedestrian and vehicle safety in windy environments. Issue 147 (December 2015) - Baker, Chris
Abstract: Recent events in the UK, in which fatalities have occurred due to the existence of high wind speeds around new developments, have highlighted the need for a consistent set of criteria that can be used to assess the effect of new buildings on the safety of vehicles and pedestrians. This paper presents a risk analysis for assessing the risk of such incidents that unifies current rather disparate methodologies, and presents a novel and consistent risk based framework for the assessment of future building developments. The paper first discusses the nature of current methodologies, and argues that methods that are based on the probability distribution of wind velocities alone are not wholly adequate. The new methodology takes the wind velocity probability distribution functions that can be obtained from wind tunnel measurements and convolutes these with the cumulative distribution functions for human and vehicle instability in high winds to give a risk of an accident occurring and the consequences of the calculated risk. It is argued that such a risk based methodology allows for greater consistency in the application of any pedestrian/vehicle movement restrictions or alleviation methods. Finally other potential applications and extensions of the method are discussed – specifically the application of the proposed methodology to wind comfort studies and also to the problem of passenger instability caused by the slipstreams of trains. Graphical abstract: Highlights: A methodology for determining the risk of accidents to humans and vehicles in windy environments. A probabalistic approach addressing the variability of wind, human and vehicle characteristics. A proper consideration of the consequences of accidents. The potential for being used in the consideration of a number of other related issues.